Prevention of Influenza Virus-Induced Immunopathology by TGF-β Produced during Allergic Asthma - Furuya, Yoichi (PLoS Pathog, 2015)
Asthma is believed to be a risk factor for influenza infection, however little experimental evidence exists to directly demonstrate the impact of asthma on susceptibility to influenza infection. Using a mouse model, we now report that asthmatic mice are actually significantly more resistant to a lethal influenza virus challenge. Notably, the observed increased resistance was not attributable to enhanced viral clearance, but instead, was due to reduced lung inflammation. Asthmatic mice exhibited a significantly reduced cytokine storm, as well as reduced total protein levels and cytotoxicity in the airways, indicators of decreased tissue injury. Further, asthmatic mice had significantly increased levels of TGF-β1 and the heightened resistance of asthmatic mice was abrogated in the absence of TGF-β receptor II. We conclude that a transient increase in TGF-β expression following acute asthma can induce protection against influenza-induced immunopathology.